3D Architecture Materials Made of NiCoAl‐LDH Nanoplates Coupled with NiCo‐Carbonate Hydroxide Nanowires Grown on Flexible Graphite Paper for Asymmetric Supercapacitors. Issue 18 (13th August 2014) - Yang, Juan; Yu, Chang; Fan, Xiaoming; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> Asymmetric supercapacitors featuring both high energy and power densities as well as a long lifespan are much sought after and may become a reality depending on the availability of cheap yet highly active electrode materials. Here, a novel flexible architecture electrode made of NiCoAl‐layered double hydroxide (NiCoAl‐LDH) nanoplates coupled with NiCo‐carbonate hydroxide (NiCo‐CH) nanowires, grown on graphite paper via an in situ, one‐step, hydrothermal method is reported. The nanowire‐like NiCo‐CH species in the nanoplate matrix function as a scaffold and support the dispersion of the NiCoAl‐LDH nanoplates, resulting in a relatively loose and open structure within the electrode matrix. Asymmetric supercapacitors fabricated using the nanohybrids as the positive electrode and a typical activated carbon (AC) as negative electrode show a high energy density of 58.9 Wh kg−1 at a power density of 0.4 kW kg−1, which is based on the total mass of active materials at a voltage of 1.6 V. An energy density of 14.9 Wh kg−1 can be retained even at a high power density of 51.5 kW kg−1. Our asymmetric supercapacitor also exhibits an excellent long cycle life, whereby a specific capacitance of 97% is retained even after 10 000 cycles.